Problems of impurities deducing from multicomponent media at thermal heating, ionization and rotation of plasma in crossed fields - Yuferov, V.B.; Katrechko, V.V.; Svichkar, A.S.; Shariy, S.V.; Tkachova, T.I.; Mufel, E.V.; Ilichova, V.О.; Pakhomov, А.Yu. (Вопросы атомной науки и техники, 2016)
The possibility of multicomponent mixtures separation at thermal heating, ionization and plasma rotation in relation to the spent nuclear fuel (SNF) is shown. At thermal heating it is possible to allocate up to 75% of impurities of fission products (FP), after which the SNF contains oxides of zirconium, niobium and lanthanides. At the stage of ionization it is impossible to deduce the lanthanide oxides, but it is possible to remove partially the oxides of zirconium and niobium. Further removal of impurities will occur in rotated plasma. Under certain conditions heavy ions will get to lateral surface of vacuum chamber, and the light ones will move along the magnetic field lines and precipitate on the collector. The molecular plasma has energy cost to excitation of vibrational and rotational degrees of freedom, dissociation. As simulation media it is advisable to use non-radioactive isotopes of spent nuclear fuel oxides. Показана можливість розділення багатокомпонентних сумішей при термонагріві, іонізації і обертанні плазми стосовно до відпрацьованого ядерного палива (ВЯП). При термонагріві можливе виділення до 75% домішок продуктів поділу (ПД), після чого у ВЯП залишаються оксиди цирконію, ніобію і лантаноїдів. На стадії іонізації неможливо вивести окисли лантаноїдів, але можливе часткове виведення окислів цирконію та ніобію. Подальше видалення домішок відбуватиметься в плазмі, що обертається. При виконанні певних умов на бічну поверхню вакуумної камери виходитимуть важкі іони, а легкі будуть рухатися уздовж силових ліній магнітного поля і осідати на колекторі. У молекулярній плазмі виникають енерговитрати на збудження коливальних і обертальних ступенів свободи, дисоціацію. В якості імітаційних середовищ доцільно використовувати окисли нерадіоактивних ізотопів ВЯП. Показана возможность разделения многокомпонентных смесей при термонагреве, ионизации и вращении плазмы применительно к отработанному ядерному топливу (ОЯТ). При термонагреве возможно выделение до 75% примесей продуктов деления (ПД), в ОЯТ остаются окислы циркония, ниобия и лантаноидов. На стадии ионизации невозможно вывести окислы лантаноидов, но возможно частичное выведение окислов циркония и ниобия. Дальнейшее удаление примесей будет происходить во вращающейся плазме. При выполнении определенных условий на боковую поверхность вакуумной камеры будут выходить тяжелые ионы, а легкие - двигаться вдоль силовых линий магнитного поля и осаждаться на коллекторе. В молекулярной плазме возникают энергозатраты на возбуждение колебательных и вращательных степеней свободы, диссоциацию. В качестве имитационных сред целесообразно использовать окислы нерадиоактивных изотопов ОЯТ.